The Effect of Competency and Motivation on Work Satisfaction and its impact on Employee Performance: The Case of DITPOLAIRUD POLDA of South Sumatera - Wulandari, Redita; Rahayu, Sri; Tobari, Tobari (International Journal of Business, Management and Economics, 2025)
This study aims to determine 1) The Effect of Competence on Job Satisfaction of Ditpolairud Polda Sumatera Selatan Personnel. 2) The Effect of Motivation on Job Satisfaction of Ditpolairud Polda Sumatera Selatan Personnel. 3) The Effect of Competence on Personnel Performance of Ditpolairud Polda Sumatera Selatan. 4) The Influence of Motivation on the Performance of Ditpolairud Polda South Sumatra Personnel. 5) The Influence of Job Satisfaction on the Performance of Ditpolairud Polda South Sumatra Personnel. This type of research is Associative. The variables used by the researcher are Competence, Motivation, Job Satisfaction, and Performance. The population of this study consisted of all Ditpolairud Polda South Sumatra Personnel, and the Sample in the study amounted to 120 people, selected using cluster random sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM). The results of this study indicate that: 1) there is a positive and significant influence of Competence on the Job Satisfaction of Ditpolairud Polda South Sumatra Personnel. 2) There is a positive and significant influence of Motivation on the Job Satisfaction of Ditpolairud Polda South Sumatra Personnel. 3) There is a positive and significant influence of Competence on the Performance of Ditpolairud Polda South Sumatra Personnel. 4) There is a positive and significant influence of Motivation on the Performance of Ditpolairud Polda South Sumatra Personnel. 5) There is a positive and significant influence of Job Satisfaction on the Performance of Ditpolairud Polda South Sumatra Personnel (6). Job Satisfaction strengthens the influence of competence on Performance (7). Job Satisfaction strengthens the influence of Motivation on Performance